2011
DOI: 10.3922/j.psns.2011.1.007
|View full text |Cite
|
Sign up to set email alerts
|

Lateral interactions in visual perception of temporal signals: Cortical and subcortical components.

Abstract: The aim of this work was to isolate and investigate subcortical and cortical lateral interactions involved in flicker perception. We quantified the perceived flicker strength (PFS) in the center of a test stimulus which was simultaneously modulated with a surround stimulus (50% Michelson contrast in both stimuli). Subjects were requested to adjust the modulation depth of a separate matching stimulus that was physically identical to the center of the test stimulus but without the surround. Using LCD goggles, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The similarities between the psychophysical and physiological results suggested that the physiological basis of the perceived flicker strength in the center stimulus was already present in the retino-geniculate pathway [26] . In additional psychophysical experiments, Teixeira et al isolated and investigated the subcortical and cortical lateral interactions involved in flicker perception using center and surround presented monoptically or dichopticallyand concluded that both subcortical and cortical lateral interactions modulated flicker perception [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between the psychophysical and physiological results suggested that the physiological basis of the perceived flicker strength in the center stimulus was already present in the retino-geniculate pathway [26] . In additional psychophysical experiments, Teixeira et al isolated and investigated the subcortical and cortical lateral interactions involved in flicker perception using center and surround presented monoptically or dichopticallyand concluded that both subcortical and cortical lateral interactions modulated flicker perception [28] .…”
Section: Discussionmentioning
confidence: 99%